Two Different Approaches of Estimating Production Factor Demand: Evidence from Indonesian Large and Medium Enterprises - Afin, Rifai (Muslim Business and Economics Review, 2025)
This study measures the elasticity of production factors of manufacturing companies in Indonesia by applying demand model for production inputs. Using survey data of large and medium-sized companies in Indonesia from 1995-2015, this study calculates the elasticity of demand for factors of production through two approaches: first, the transcendental logarithm equations applying unrestricted, homotheticity, and adjustment cost model, and second, a system of equations. We use the variation in the group of industries as a proxy for the market price of inputs. The results show that there is heterogeneity in terms of the magnitude and nature of the cross-price elasticity between production inputs for both complementary and substitute inputs. Meanwhile, the own price elasticity is negative for all production inputs and there are positive effect adjustment costs that must be borne by firms in expanding production inputs.